Masaru Ibuka [videorecording] facing the challenge of creation. (In prosperity's wake : portraits of post-war economy)
Traces the development of Japan's economy after World War II. It focuses on the role of Masaru Ibuka who succeeded in putting the transistor into use and caused a revolution in the world of electronic products world-wide.